Local Antibiogram Predicts Appropriate Antibiotic Selection for Prostate Biopsy Prophylaxis. Issue 2 (March 2019) - Rourke, Elizabeth; Madsen, Steven; Yunes, Andrea; Basler, Joseph; Liss, Michael A.
Abstract: Introduction: We evaluated our local antibiogram to determine the accuracy of its use in antibiotic augmentation before transrectal prostate biopsy. Methods: We analyzed pre-transrectal prostate biopsy rectal swabs from January 2016 to September 2017 at the South Texas Veterans Health Care System (STVHCS). A query was run on pre-procedure rectal swabs positive for fluoroquinolone resistance in men undergoing transrectal prostate biopsy during this time. Culture results and antibiotic resistance profiles were recorded and compared to the proportion of antibiotic resistance in the STVHCS 2016 antibiogram. Results: We identified 611 patients who underwent rectal culture before transrectal prostate biopsy, of which 98 were ciprofloxacin resistant Escherichia coli isolates. Our cohort demonstrated 80% sensitivity to ciprofloxacin compared to the STVHCS antibiogram sensitivity of 65% (p <0.001). Gentamicin demonstrated similar sensitivities between the antibiogram and cohort (90% and 88%, respectively). There were no statistically significant differences between the STVHCS antibiogram and the sensitivity profiles of our rectal swab cohort except for ampicillin/sulbactam, which was 57% in the antibiogram and 32% in our cohort (p=0.019). Of the ciprofloxacin resistant E. coli identified 4% (4 of 98) were considered extended spectrum beta-lactamase producers. Conclusions: Overall, resistance patterns in ciprofloxacin resistant E. coli isolates from our study population are consistent with the STVHCS antibiogram. Therefore, a local antibiogram may be used in an implementation strategy for targeted antibiotics or augmentation of fluoroquinolone prophylaxis for transrectal prostate biopsy.